The Small Business Controller - Hanson, Richard O (Business Expert, 2012)
This book describes the role of the controller in a small business and provides a detailed “how-to” analysis of the many duties and responsibilities the small business controller often assumes. This work, based on approximately 30 years of working relationships with many small businesses, describes the functions many controllers of small businesses perform as well as specifi c elements they need to consider when performing specialized functions.